HUBUNGAN DUKUNGAN SUAMI DENGAN PENGGUNAAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR - Anik Puji Rahayu (ITKES Wiyata Husada Samarinda, 2018)
Background: Contraception services are one of the types of family planning services available. Most family planning acceptors choose and pay for themselves various types of contraception available.Objective: The purpose of this study was to determine the relationship of husband's support to the use of contraception in couples of childbearing age in the Air Putih Sub-District of Samarinda Ulu District.Method: The method of this research is Descriptive Correlation, with a cross sectional design. The sampling technique used in this study is Non Probability Sampling with a sample of 49 respondents data collected using a questionnaire measuring instrument.Results: Fisher test results obtained a value of P = 1,000> alpha = 0.05, it can be concluded that there was no relationship between husband's support and the use of contraception in couples of childbearing age in the Air Putih Sub-District of Samarinda Ulu District.Conclusion: There is no relationship between husband's support and the use of contraceptives in couples of childbearing age in the Air Putih Sub-District of Samarinda Ulu District